The Influence of Digital Mindset, Digital Competence and Leadership Style on Employee Career Development - Hazni, Elvira; Nurhaida, Ida (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The effect of Digital Mindset, Digital Competence and Leadership Style on Career Development is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) Digital Mindset has an effect on Career Development; 2) Digital Competence has an effect on Career Development; and 3) Leadership Style has an effect on Career Development.